Stating Rules or Imparting Knowledge? An Intervention Experiment on the Trust and Sharing of Seismic Rumors in the Beijing-Tianjin-Hebei Area of China - Lei Sun; Jun Guo; Xingyu Liu (International Journal of Disaster Risk Science)
Abstract Seismic rumors can mislead the public and trigger unnecessary actions, underscoring the importance of their control in disaster management. This study examined the impact of two different intervention tools—rule-based intervention and knowledge-based intervention—on the trust and sharing of seismic rumors. We designed a survey experiment to explore this issue, and 500 respondents participated in the experiment. The results indicate that the rule-based intervention significantly reduced the public’s trust in and intention to share seismic rumors, but the knowledge-based intervention failed. Possible mechanisms are that the rule-based intervention raises awareness of the unreliability of disaster information sources and costs associated with sharing rumors. It is suggested that communicating the existing rules and policies regarding disaster information release might be an effective approach to rendering disaster rumors uncreditable and then reducing people’s intention to share. These findings enrich our understanding of the effectiveness of different intervention tools regarding rumor behavior in disaster scenarios and offer insights for practical seismic rumor management.